2017
DOI: 10.1259/dmfr.20160280
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the temporomandibular joint: comparison between acquisitions at 7.0 T using dielectric pads and 3.0 T

Abstract: Objectives: To qualitatively and quantitatively compare MRI of the temporomandibular joint (TMJ) at 7.0 T using high-permittivity dielectric pads and 3.0 T using a clinical highresolution protocol. Methods: Institutional review board-approved study with written informed consent. 12 asymptomatic volunteers were imaged at 7.0 and 3.0 T using 32-channel head coils. Highpermittivity dielectric pads consisting of barium titanate in deuterated suspension were used for imaging at 7.0 T. Imaging protocol consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…With the increase of the contrast-to-noise ratio (CNR) and SNR, the quality of MR images improves [39]. Kuhn et al [40] analyzed imaging at 7.0 T vs. 3.0 T and found that although both methods had similar SNR, the visibility of articular disc was significantly better at 7.0 T imaging. Furthermore, Sun et al [39] compared two different types of coils in TMJ MR imaging: a 15-channel phased array head coil and 6-channel dS Flex M surface coil.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…With the increase of the contrast-to-noise ratio (CNR) and SNR, the quality of MR images improves [39]. Kuhn et al [40] analyzed imaging at 7.0 T vs. 3.0 T and found that although both methods had similar SNR, the visibility of articular disc was significantly better at 7.0 T imaging. Furthermore, Sun et al [39] compared two different types of coils in TMJ MR imaging: a 15-channel phased array head coil and 6-channel dS Flex M surface coil.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…In addition to this, MRI interpretations are still falling short of showing a clear association with reported symptoms [ 7 ]. Furthermore, the impact of potential imaging findings on treatment choice and clinical outcome is still controversial, suggesting that the depiction of TMJ in clinical routine is still unsatisfactory and may benefit from further optimization [ 8 ]. Moreover, it was also indicated that, often, there is still an unclear correlation between clinical signs and symptoms and imaging findings in all TMD patient groups [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…RF coils can be divided into orthogonal, phased array, surface flexible, intraoperative, and array types. 25 The selection and reasonable application of the RF coil are the most important components. The phased array coils are composed of multiple single coils, which can provide more detailed MRI information for the inspected position.…”
Section: Discussionmentioning
confidence: 99%
“…The soft surface coil is used to cover a limited area of the body during MRI, which can use the structure’s characteristics to bring the coil as close to the detected position as possible to improve image quality. 16,24 In our study, the head coil that consists of a basilar coil and its upper coil is a phased array coil 25,26 ; it is equipped with a supporting platform with a built-in rear coil for the head examination (30 cm, 15 channels). The dS Flex surface coil, which is mainly used for imaging small joints and limited regions, is a loop coil with a pedestal on the bottom and an annular integrated flex coil.…”
Section: Discussionmentioning
confidence: 99%